A method of estimating the vertical component of gusts in turbulence in the upper air - VENKITESHWARAN, S. P.; HUDDAR, B. B. (MAUSAM, 1966)
It has been shown how the rate of rotation of the fan in the F-type radiosonde can be used to locate regions of turbalence in the upper air. A method of estimating the vertical component of the gusts from the radiosonde records is described in this paper. The mean rate of rotation of the fan at different heights has been obtained from a number of flights when no turbulence is present. This decreases uniformly with height due to the decrease in density of the air. Tests conducted in a wind tunnel give the rate of rotation of the fan for different speeds of wind in the direction of the axis of the fan. From these values, it has been shown how the vertical component of the gust in regions of turbulence can be estimated.